Anillin propels myosin-independent constriction of actin rings - Kučera, Ondřej; Siahaan, Valerie; Janda, Daniel; Dijkstra, Sietske H; Pilátová, Eliška; Žatecká, Eva; Diez, Stefan; Braun, Marcus; Lansky, Zdenek (Nature communications, 2021)
Constriction of the cytokinetic ring, a circular structure of actin filaments, is an essential step during cell division. Mechanical forces driving the constriction are attributed to myosin motor proteins, which slide actin filaments along each other. However, in multiple organisms, ring constriction has been reported to be myosin independent. How actin rings constrict in the absence of motor activity remains unclear. Here, we demonstrate that anillin, a non-motor actin crosslinker, indispensable during cytokinesis, autonomously propels the contractility of actin bundles. Anillin generates contractile forces of tens of pico-Newtons to maximise the lengths of overlaps between bundled actin filaments. The contractility is enhanced by actin disassembly. When multiple actin filaments are arranged into a ring, this contractility leads to ring constriction. Our results indicate that passive actin crosslinkers can substitute for the activity of molecular motors to generate contractile forces in a variety of actin networks, including the cytokinetic ring.
Keywords: buněčné dělení; Humans; mikrofilamenta; Drosophila melanogaster; zvířata; Contractile Proteins; Microfilament Proteins; Myosins; aktomyosin; myosiny; kontraktilní proteiny; Animals; Cytokinesis; lidé; Actin Cytoskeleton; mikrofilamentové proteiny; Actins; aktiny; Actomyosin; Cell Division; cytokineze